Empathy and Compassion as a Caring Personality and Their Functional Neuroimaging in theBrain: A Literature Review - Kuntarti Kuntarti; Yeni Rustina (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
The development of caring personalities such as empathy and compassion is crucial for successful therapeutic interaction for human-related professional. The scientific studies have recently revealed functional neural plasticity associated with the training of empathy and compassion. This article reviews the functional neuroimaging of empathy and compassion in the brain. The recent studies have given insights that empathy increased the negative effect and brain activation in the anterior insula and anterior midcingulate cortex brain that associated with empathy for pain and compassion increased the positive effect and brain activation in the ventral striatum, progenual anterior cingulate cortex, and medial orbitofrontal cortex brain. These results indicate that human-related professional such as nurses, psychologists, and other health professionals can feel empathy as pain or distress if these feelings occur continuously as experienced by them. However, the compassion program can reducethis condition. These findings suggest that the cultivation of compassion can be design as a program to maintain empathy and increase resilience and coping strategies in health care, educational setting, and high-stress environment.